Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1080/09168451.2015.1027652
|View full text |Cite
|
Sign up to set email alerts
|

New acylated anthocyanins from purple yam and their antioxidant activity

Abstract: Purple yam (Dioscorea alata L.), which is widely distributed in tropical and subtropical regions, is characterized by its color and viscosity. Previous studies have shown that purple yams contain a variety of acylated anthocyanins that exhibit higher levels of antioxidant activity than the corresponding nonacylated compounds. In this study, the pigments found in purple yams from the Philippines (D. alata) were isolated and evaluated in terms of antioxidant activity. Four new acylated anthocyanins, alanins (1–4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…Mass spectral characteristics of the extract indicated that peaks 1, 4, and 7 had the same precursor [M] + at 611 but different retention times. From their fragmentation patterns, they were most likely cyanidin glycoside isomers, which are commonly found in Dioscorea species [ 2 , 12 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mass spectral characteristics of the extract indicated that peaks 1, 4, and 7 had the same precursor [M] + at 611 but different retention times. From their fragmentation patterns, they were most likely cyanidin glycoside isomers, which are commonly found in Dioscorea species [ 2 , 12 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some yam species have attractive purplish colours, i.e., D. alata or ube yam from the Philippines, raja-ala from Sri Lanka [ 11 ], and D. trifida L. from South America [ 12 ]. Anthocyanins in D. alata are cyanidin–based such as cyanidin 3- O -gentiobioside; alatanin 1 [ 13 ]; alatanin 2 [ 13 ]; alatanins A, B, and C [ 14 ]; and alatanins D, E, F, and G [ 15 ]. The purple pigment in D. trifida L., however, was mainly peonidin glycoside [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The root color of purple yam (D. alata) is attributed to the high content of anthocyanins which exhibit significant antibacterial activities [212], anti-inflammatory effects on trinitrobenzenesulfonic acid (TNBS)-induced colitis in mice [213], antiglycative properties [214], and antidiabetic properties [215,216]. The main detected anthocyanins in this species were identified as cyanidin, pelargonidin, and peonidin-type compounds and alatanins A-C [43]; however, the individual compound profile and the overall anthocyanin content are affected by maturity stage and the expression of the concomitant genes [44]. Apart from D. alata, which is considered the main purple yam, there are also cultivars of D. trifida or cush-cush yam which contain peonidin, cyanidin, and pelargonidin aglycones [45].…”
Section: Yammentioning
confidence: 99%
“…Cyanidin, pelargonidin, and peonidin-type compounds; alatanins A-C Cyanidin 3-hexoside acylated with two hydroxycinnamic acids, cyanidin 3-glycoside acylated with one hydroxycinnamic acid, cyanidin 3-glycoside acylated with one hydroxycinnamic acid, peonidin 3-glycoside acylated with one hydroxycinnamic acid, alatanin-C [43][44][45][46] Yellow Carotenoids β-Carotene [47] Onion (Allium cepa L.) Bulb (swollen basis of leaves) Purple Flavonols and acylated and non-acylated cyanidin glucosides Dihydroflavonol taxifolin and its 3-, 7-, and 4 -glucosides [48,49] Radish (Raphanus sativus L.) Taproot (swollen root and hypocotyl)…”
Section: Purplementioning
confidence: 99%
“…cyanidin-3-rhamnoglucoside; (Lula et al, 2015) hydro-Q chromene; gamma-tocopherol-9; RRR-alpha-tocopherol; coenzyme Q; 1-feruloylglycerol; (Cheng et al, 2007) 4-Phenylbutan-2-one; (Gramshaw and Osinowo, 1982) alanins, cyaniding, peonidin (Moriya et al, 2015) in D alata. In Bangladesh traditionally it is used against leprosy and tumor.…”
mentioning
confidence: 99%